Ultrasonic Drug Delivery Using Micelles and Liposomes - Martins, Ana M. (2016)
The encapsulation of drugs in nanocarriers revolutionized research in drug delivery, especially in cancer chemotherapeutics. Several nanosystems have been developed including liposomes, polymeric micelles, dendrimers, solid lipid nanoparticles, and others. The surface of nanocarriers can be modified to alter their characteristics and improve their efficiency as drug delivery systems. The addition of polyethylene glycol chains, for example, increases the blood circulation time of nanocapsules and, in some cases, improves their stability. Once the structure of nanocarriers is optimized, the next logical step is to explore the feasibility of using one or several trigger mechanisms to release their therapeutic contents at the required time and space. Abundant literature is available on both internal and external trigger mechanisms in cancer drug delivery. Internal mechanisms include changes in pH, enzyme concentration, and temperature, while external mechanisms include light, magnetic/electromagnetic waves, and acoustic power. This review focuses on the utility of ultrasound and polymeric micelles in cancer drug delivery. The idea is to control the release of chemotherapeutics from micelles to cancerous cells by focusing the ultrasound waves on the diseased tissue while sparing other healthy cells in the body. Thus, the side effects of conventional chemotherapy can be minimized.